A new and correct map of North America, with the West India Islands, divided according to the last Treaty of Peace, Concluded at Paris, the 20th of Jan. 1783, wherein are particularly Distinguished, the thirteen Provinces wich Compose The United States of North America- [arkusz 2] - Lotter, Tobias Conrad (1717-1777) (Lotter, Tobias Conrad (1717-1777), 1784)
miedzioryt ręcznie kolorowany [skala około 1:5 300 000] 1 mapa w 4 arkuszach, legenda, mapy poboczne: A Particular Map of Baffin and Hudson's Bay The Passage by Land to California Discover'd by Father Eusebius Francis Kino podziałka liniowa: Geometrical Miles 60 to a Degree: 255 – 8,5 cm opis fiz.: około 50x57cm